Interaction Between Dimensions Forming the Human Development Index - Sangur, Korneles; Leiwakabessy, Erly (Jurnal Informatika Ekonomi Bisnis, 2025)
This study covers the three dimensions that make up the HDI to know the mutual influence between the dimensions of decent living standards, health, and education. The research method used is the Panel Vector Auto Regression method. The data used is panel data consisting of 11 districts/cities in Maluku Province during 2010-2022. The decent standard of living dimension and the Health dimension have a two-way effect, the same condition occurs in the Health and Education dimensions. The decent standard of living dimension only has a unidirectional influence on the Education dimension. The results of the Implus Response Function show that all dimensions in the model have a permanent response due to a shock from another dimension. Variance decomposition results show that only the Health dimension has a smaller proportion of series movement due to the shock of the dimension itself compared to the shock of the decent standard of living dimension. The application of this research is to provide a point of view for policymakers, that to improve the welfare of the community as measured by HDI, the policies designed need to stimulate all dimensions of HDI externally and also build harmonization between dimensions so that they influence each other and encourage an increase in HDI internally.